The Cytoprotective Effect of Crocin on Oxaliplatin Treated VERO cell line In Vitro Study - Sameer H. Abboud; Hamid Naji Obied; Hassanien F. Hassan (Kufa Journal for Veterinary Medical Sciences, 2017)
Abstract Background Cancer is a disease characterized by a shifted in the control mechanism that governs cell survival, proliferation and differentiation. There are many types of treatment to the cancer like surgery, radiation, chemotherapy, immunotherapy and others. Each of these above treatments has its indication effect and has Sid effect and / or adverse effect. The chemotherapy is one type of this treatment to the cancer that have the indication effect, side effect and adverse effect. There are many type of chemotherapeutic agent that used for this type of cancer one of them it is platinum compound (cisplatin, oxaliplatin and others). There are two types of limitation in the use of these agents one of them is the side effect which is neurotoxicity, Ototoxicity, nephrotoxicity, and etc. and the second one is the resistance of cancer cells to these agents. Aim of the study Taste the cytoprotection effect of Crocin on oxaliplatin treated VERO cell line Material and methods:- By using the tissue culture techniques which is a newly used techniques to check the cytotoxicity of many compound and the expected mechanism of action these techniques made a good jump in the research in many field In this study we use VERO cell line and after exposure of this cell line firstly to different concentrations of oxaliplatin ( 1, 0.5, 0.25 and 0.125 mg/ml) for 48hr, secondly to different concentrations of Crocin (0.5, 0.25 and 0.125 mg/ ml ) for 48hr. And thirdly to mix concentrations of oxaliplatin and Crocin in 48hr for the VERO cell line and measure the cytotoxicity of these exposures by crystal violet test (C.V. test) to show and compare the effect of these agents specially the Crocin. The oxaliplatin has cytotoxic effect, its inhibitory concentration 50% (IC50) in 48hr is (0.031mg/ml) which is the maximum cytotoxic effect in vitro. While the Crocin don’t have cytotoxic effect at this tested concentration and for this cell line. After mixed different concentration of Crocin with different concentration of oxaliplatin the cytotoxicity of oxaliplatin reduce significantly. Conclusion:- From our study we can conclude the following:- The Crocin has cytoprotective effect. The Crocin has no anti tumor and anti proliferative activity within these tasted concentration and this cell line